Intra-muscular hemangioma: A review - Shruti Nayak; Amarnath Shenoy (Wolters Kluwer Medknow Publications, 2014)
Intra-muscular hemangiomas (IMH) are relatively uncommon benign vascular tumors, which account for less than 1% of all hemangiomas. IMH may be presented as a perceived sporting injury. Diagnosis of this lesion is important not only because of its rarity, but also due to dangers posed by misdiagnosis and mismanagement. They must be considered in the differential diagnosis of unexplained pain and swelling in muscles. IMH occurring in the oral cavity is reviewed below.